Curriculum Development Strategies in Facing Competency Demands at Sepaso Bengalon Junior High School - Siti Sri Fattul Jannah; Faelasup (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study aims to describe the curriculum development strategy at Sepaso Bengalon Junior High School and what obstacles the school will face when developing the curriculum. This research utilizes data collection techniques in terms of document analysis, interviews, observation, and documentation. The results of this data research can be concluded that in the framework of the implications of curriculum development strategies, there are several stages, namely assessing the needs in accordance with the school situation, conceptualizing curriculum planning, developing plans to implement the curriculum, implementing the curriculum in the field, carrying out curriculum assessment and monitoring, and carrying out improvements according to the evaluation results when developing the curriculum. Meanwhile, in developing the curriculum, there will definitely be some obstacles that will be experienced by the school. For example, inadequate facilities and infrastructure so that an educator cannot maximize the teaching and learning process. By updating and improving the curriculum system continuously, it will help especially for an educator in order to keep the material taught relevant to the times and the needs of the community.